Analis Etos Kerja Islam terhadap Kinerja Karyawan Toko Dimas di Kecamatan Pakusari - Maulana Firmansyah; Aniqotuzzuhro' Fitriana (Medan Resource Center, 2023)
Islamic work ethic is an attitude or character of a person in carrying out an activity or work, in this case a company can analyze employee performance and then evaluate it. The researcher raised this topic because there were problems related to the Islamic work ethic and the performance of dimas shop employees, where dimas shop employees still did not have a sense of responsibility for their work. The purpose of this research is to find out how the performance of Toko Dimas employees is, as well as the leadership patterns that are applied so that employees remain disciplined. The method used in this research is to use a qualitative approach. The main subject of our research is the Dimas shop, which consists of the Dimas shop leader, 6 Dimas shop employees, Dimas shop customers. The sampling technique used snowball sampling and case study. According to our hypothesis, there are some employees who do not have a good enough work ethic and performance. The problems we found in the field were about compensation or expecting rewards from customers or buyers, in fact Dimas shop employees already receive a salary every month. The conclusion that we can draw from this research is that dimas store employees already have an Islamic work ethic and good employee performance, but the expectation of rewards causes employees to be slow/negligent in carrying out their duties